A fast adaptive bus voltage regulation strategy for supercapacitor energy storage systems. Issue 12 (21st April 2022) - Shi, Zhiyuan; Peng, Jun; Li, Heng; Peng, Hui; Liu, Weirong; Gao, Zhiwei; Huang, Zhiwu
Abstract: Supercapacitors undergo wide terminal voltage fluctuations, which makes it difficult to maintain a stable bus voltage and develop a satisfactory dynamic response. To solve this problem, a fast adaptive bus voltage regulation strategy is proposed in this paper. Firstly, the dual‐loop controller with an external voltage loop and an internal current loop is applied to the supercapacitor energy storage systems. Secondly, an adaptive proportional–integral controller is designed for the outer voltage loop to accommodate the variations of the system characteristics. Furthermore, in order to improve the dynamic response, the set‐point automatic modulation is integrated into the voltage control loop to compensate the stochastic load demanded fluctuations. The simulation and experimental results show that the proposed method ensures the stability of the bus voltage and provides a lower fluctuation and shorter settling time compared with the conventional method.